Studies on veterinary medicine - Mandelker, Lester; Vajdovich, Peter; SpringerLink (Online service). (Totowa, NJ Humana Press, 2011)
This compendium of research material on the role of oxidative stress in animal disease and morbidity examines both the general and the specific. Sourced from scientists, veterinarians, and members of the medical community from around the world, it includes chapters on our wider understanding of the corrosive function of free radicals in cell biology as well as focusing on the interplay between oxidative stress and metabolism in a variety of animal species including dogs, ruminants and birds.   Since biogerontologist Denham Harman first posited that free radicals arising from the metabolic activity of oxygen play a central role in aging and disease, a mass of evidence has accumulated linking oxidative stress and biological degradation. We now understand that living in an aerobic environment inevitably leads to the production of free radicals that go on to attack biological membranes and lipoproteins via oxidation in a process called lipid peroxidation. Reacting with carbon-based molecules such as polyunsaturated fatty acids, these free radicals cause oxidative stress and tissue damage.   The purpose of Studies on Veterinary Medicine is to inform clinicians, students and others of the plethora of consequences that free radical damage (ROS) has on various cells, tissues, and organs, as well as in different species of animals. The chapters also analyze the effects of oxidative stress on aging and various morbidities such as diabetes, cognitive dysfunction and heart disease. Contributors variously present their interpretation of the role played by oxidative damage in disease and assess the benefits of antioxidant therapies.
Preface -- 1. Oxidative Stress, Free Radicals and Cellular Damage, Lester Mandelker DVM -- 2. Use of free radicals and antioxidants in inflammatory processes of animals Peter Vajdovich DVM, PHD -- 3. Oxidative Stress and Calcium Metabolism, Patricia Schenck DVM, PHD -- 4. TRPM2 Cation Channels and Oxidative Stress-Induced Neuronal Cell Death Mustafa Naz?ro?lu1, PHD -- 5. Oxidative stress in diabetes mellitus Stefano Comazzi, DVM, PHD -- 6. Oxidative Stress in the Spinal Cord of Dogs and Cats Wendy Baltzer, DVM, PhD -- 7. Oxidative Stress, Cognitive Dysfunction and Brain Aging Elizabeth Head, Ph.D.,* and Steven C. Zicker DVM, PhD -- 8. The role of oxidative stress in ocular disease Gustavo L. Zapata PHD -- 9. Oxidative Stress in Heart Failure Gordon Moe, MD, MSc -- 10. Nutrient Selection in the Management of Canine Atopic Dermatitis John Kuck DVM -- 11. Avian antioxidants and oxidative stress: highlights from studies of food, physiology, and feathers Kevin McGraw DVM -- 12. Free Radicals and Antioxidants in Avian Diseases Miklós Mézes, PhD and Krisztián Balogh, PhD -- 13. Oxidative Stress In Ruminants Pietro Celi (DVM, PhD) -- 14. Antioxidant Effects of Supplements Lester Mandelker DVM and Peter Vajdovich DVM, PHD.
Electronic reproduction.
Keywords: Veterinary medicine; Oxidative stress; Electronic books